(untitled) (ModaPalavra e-periódico, 2021)
Visual Management combined with Service Design tools is a good strategy for implementing process mapping in remote scenarios. The general objective of this study was to present its concepts and implement the service blueprint as a facilitating tool for mapping the experiences of processes in the Human Resources area. To provide the best interaction and practice of actions, an action research was carried out at the company Jungle Devs, mapping the entire journey of the selection process for new candidates. The methodological procedure was oriented by the guidelines of the exploratory research, starting from a systematic understanding of the processes that took place in person and from the analysis of the activities performed by the company. A greater understanding of the activities of the company’s employees and of the interaction with the candidates was sought, thus identifying the problematic points and from these, the development of recommendations for improvement and formalization of the process in the remote mode.